Transparent Ceramic@Sapphire Composites for High‐Power Laser‐Driven Lighting - Guoyu Xi; Shisheng Lin; Tongjie Shen; Tao Pang; Zikang Yu; Yang Peng; Lingwei Zeng; Yuxiang Ke; Zhehong Zhou; Ronghua Chen; Feng Huang; Daqin Chen (Advanced Science, 2025)
Abstract Although phosphor ceramics are promising candidates for high‐power laser lighting applications, their performance is seriously restricted by luminance saturation effects. This study proposes a novel transparent ceramic@sapphire composite material design, fabricated via a straightforward high‐temperature sintering process, which differs from the conventional approach of incorporating high‐thermal‐conductivity microcrystalline grains. This kind of composite can effectively avoid luminescence grain dilution, and deliver significantly enhanced thermal conductivity (36.9 W·m−1K−1) alongside superior luminescence performance. This strategy demonstrates exceptional versatility across various ceramic systems, delivering luminescence improvements of 152–319% and enhancing luminance saturation thresholds by 100–233%, relative to traditional ceramic converters. Using Lu2‐xCaMg2Si3O12: xCe3+@sapphire as a representative example, the optimized composite enables substantial enhancements in luminous flux (5902 lm) and luminous efficacy (148 lm W−1) under blue laser excitation. Compared with commercial counterparts, practical applications in automotive headlights further validate the potential of this design, offering far higher luminance intensity, extended illumination distances (> 400 m), and more uniform color distribution. This study provides a scalable and universal strategy for advancing next‐generation solid‐state lighting.